Shifting of The 'Cultural Identity' Theme in The Film Adaptation 'Hujan Bulan Juni' - Cut Novita Srikandi (English Teaching and Linguistics Journal (ETLiJ), 2022)
This study aims to investigate the shifts that appear in two texts, films and novels. The two texts are the FilmHujan Bulan Juniwhich is a movie adaptation from the novel of the same title written by Sapardi Djoko Damono. This study begins by comparing the differences and similarities between the two texts. This analysis focuses on the narrative aspects of novels and films as part of literature. As part of the study of film literature that focuses on the issue of adaptation from one medium to another, this research examines the confluence and differences of two media forms - textual and visual. The selection of narrative elements used by the film director to be transferred and which other visual methods and formats are used will also be examined. The results of the study indicate that there is a significant difference between the source text (novel) and the transfer of the film. These differences are related to the narrative structure, the role and perspective of the narrator and ideological understanding related to the theme of cultural identity.